2020
DOI: 10.1101/2020.02.06.937169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing performance of pathogenicity predictors using clinically-relevant variant datasets

Abstract: 15Purpose: Pathogenicity predictors are an integral part of genomic variant interpretation but, despite 16 their widespread usage, an independent validation of performance using a clinically-relevant dataset 17has not been undertaken. 18 19Methods: We derive two validation datasets: an "open" dataset containing variants extracted from 20 publicly-available databases, similar to those commonly applied in previous benchmarking exercises, 21 and a "clinically-representative" dataset containing variants identifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
2
11
1
Order By: Relevance
“…To evaluate the likelihood of pathogenic variant effects, we combined the distribution of known pathogenic and benign variants with computational pathogenicity scores for all biologically possible missense variants of KCNA2 . The REVEL meta-score combines variant annotations of 13 individual pathogenicity scores and showed high overall performance in the discrimination of pathogenic and benign variants in large clinical datasets [ 42 , 43 ]. High REVEL scores overlap with areas of pathogenic variant enrichment in KCNA2 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the likelihood of pathogenic variant effects, we combined the distribution of known pathogenic and benign variants with computational pathogenicity scores for all biologically possible missense variants of KCNA2 . The REVEL meta-score combines variant annotations of 13 individual pathogenicity scores and showed high overall performance in the discrimination of pathogenic and benign variants in large clinical datasets [ 42 , 43 ]. High REVEL scores overlap with areas of pathogenic variant enrichment in KCNA2 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The output of the analysis was a numerical score between 0 and 1, pathogenicity threshold for SIFT is ≤0.05, PloyPhen-2 ≥0.909 is probably damaging, and 0.447–0.908 is possibly damaging. Variants with SIFT prediction scores more than 0.05 (Guryev et al , 2004; Livingston et al , 2004; Gunning et al , 2021) and PolyPhen-2 prediction scores less than 0.447 (Guryev et al , 2004; Livingston et al , 2004; Gunning et al , 2021) were removed. Association analysis was performed on the SHEsisPlus online software platform (http://shesisplus.bio-x.cn/) (Shi and He, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Differences were also observed depending on the type of functional elements: DeepSEA, GWAVA and LINSIGHT performed better with variants in promoters and CADD with intronic variants. In another study (Gunning et al 2020), all scores were found to perform worse when, in the testing set, pathogenic variants were selected from diagnostic panels rather than among variants annotated as pathogenic in public databases. This could probably be explained by the fact that it is from these latter databases that most of the methods choose their training set.…”
Section: Pathogenicity Scoresmentioning
confidence: 98%
“…This is the method recommended in the ACMG guidelines (Richards et al 2015) but without any precision on which scores should be used and how many of these scores should be concordant. However, this simple method was shown to perform much worse than methods that integrate different scores into a single model (Gunning et al 2020). Several integrating methods have been proposed that use different scores and different models to combine them.…”
Section: Pathogenicity Scoresmentioning
confidence: 99%